On the Carleman classes of vectors of a scalar type spectral operator - Marat V. Markin (International Journal of Mathematics and Mathematical Sciences)
The Carleman classes of a scalar type spectral operator in a reflexive Banach space are characterized in terms of the operator's resolution of the identity. A theorem of the Paley-Wiener type is considered as an application.